PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR AKUNTANSI SISWA KELAS XI AKUNTANSI DI SMK NEGERI 1 GOWA - ,, Hajariah; Hasyim, Ahmad (STKIP Pembangunan Indonesia Makassar, 2019)
The main objectives of this research are: Improving the learning outcomes of Class XI Accounting Students through the application of Problem Based Learning learning models at State 1 Gowa Vocational School. This type of research is Classroom Action Research (CAR). This research was carried out on 32 subjects of XI Accounting research at State 1 Gowa Vocational School. The results showed that: The application of the Problem Based Learning learning model could improve the accounting learning outcomes of the 11th grade students of Accounting at the State Vocational School 1 Gowa